2021
DOI: 10.3390/su13147908
|View full text |Cite
|
Sign up to set email alerts
|

Mobility Trends before and after the Pandemic Outbreak: Analyzing the Metropolitan Area of Barcelona through the Lens of Equality and Sustainability

Abstract: The spatial arrangement of a metropolis is of utmost importance to carry out daily activities, which are constrained by space and time. Accessibility is not only shaped by the spatial and temporal dimension, but it is also defined by individual characteristics, such as gender, impairments, or socioeconomic characteristics of the citizens living or commuting in this area. This study analyzes mobility trends and patterns in the metropolitan area of Barcelona before and after the COVID-19 pandemic outbreak, with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 23 publications
1
10
0
Order By: Relevance
“…The daily movement of women was significantly different from that of men in all types of mobility except for self‐realization. In general, women tended to move less and to stay at home more than men, similar to what has been previously described by Bulteau et al (2022), Mejía‐Dorantes et al (2021) and Politis et al (2021). These decisions were not based on rational logic as the direct risks of the disease were greater for male patients (Peckham et al, 2020).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The daily movement of women was significantly different from that of men in all types of mobility except for self‐realization. In general, women tended to move less and to stay at home more than men, similar to what has been previously described by Bulteau et al (2022), Mejía‐Dorantes et al (2021) and Politis et al (2021). These decisions were not based on rational logic as the direct risks of the disease were greater for male patients (Peckham et al, 2020).…”
Section: Discussionsupporting
confidence: 88%
“…They also saw larger decreases in their mobility after school closures (Caselli et al, 2022), and regained more mobility after schools reopened (Bulteau et al, 2022). Further, during periods of lockdown, men took more out‐of‐household trips than women (Bulteau et al, 2022; Mejía‐Dorantes et al, 2021; Politis et al, 2021). Similarly, the effect of NPIs on mobility differed across age groups.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, boosting economic development is a priority for social sustainable development. In addition, not only in some of the literature [1, [63][64][65][66], but also in our own work, we have found that regulating social policies to transform gender norms-such as improving women's political participation status, promoting women to enter the core position of society, and correcting the traditional gender norms through concept education, training, propaganda etc.-plays a positive role in gender equality, and benefits the development of social sustainability. Moreover, these research results further indicate that promoting economic development, the governance of the sex ratio imbalance, the improvement of government-provided childcare services, and setting up the elderly care system could also create favorable conditions for gender equality and sustainable social development.…”
Section: Discussionmentioning
confidence: 52%
“…It is increasingly recognized that the traditional prioritization of private car mobility in urban transport planning comes with substantial equity effects as car ownership tends to be highest among middle-aged, males, and people with high income. In line with the heightened focus on sustainability issues, equity considerations have been receiving increased attention in transport planning (e.g., Lyons, 2021;Mejía-Dorantes et al, 2021). Expanding public transport is highlighted in Target 11.2 of the UN Sustainable Development Goals as a primary way of providing safe, affordable, accessible and sustainable transport for all, in particular those in vulnerable situations, women, children, persons with disabilities and older persons (UN, 2015).…”
Section: Equity Considerationsmentioning
confidence: 99%
“…The propensity to continue using public transport has been higher among people in lower social groups in terms of income, employment rate, education, etc. (Almlöf et al, 2021;Hu and Chen, 2021;Mejía-Dorantes et al, 2021;Palm et al, 2021). These effects likely arise from a combination of factors, including a lesser ability to work from home and lower access to private car options (Hasselwander et al, 2021).…”
Section: Equity Effectsmentioning
confidence: 99%